ANALISIS PROMOSI KESEHATAN BERDASARKAN OTTAWA CHARTER DI RS ONKOLOGI SURABAYA - Zelbi Windarini Tiraihati (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2017)
Health promotion in hospitals have a purpose to  increase public knowledge by conducting, counseling, education and training, and strengthening humanresources to raise awareness, willingness and ability of people to live a clean and healthy. Health promotion in hospital can give the benefits to the hospitalnot only in phisically sides or currative phase. The purpose of writing this article isto discuss the implementation of health promotion efforts based on Ottawa Charter at Surabaya Oncology hospital. The method used in this research is descriptive qualitative approach by direct observation and indepth interview. The implementation of health promotion on Onkologi Surabaya Hospital based on the five point of strategy health promotion in Ottawa Charter which are health public policy, supportive enviroment, reorient health services, personal skill, and community action has been appropriate. This is evidenced by the availability of mediathat support the implementation of health promotion, policy and the establishmentthe committee of PKRS. Also there are an effort to make community development as well as improving the skills of the individual in maintaining the health of the healthyindividuals as well as improve the health of the sick patient. The implementation of health promotion in hospital hopefully can make the patien’s  family can help  the patien not to infect the others especially to the family and their close friend. It also can make the patien increase their quality of living. Suggestion for Onkologi Hospital Surabaya based on the results of this study is to improve the evaluation system by conducting an evaluation in accordance with the rules that have been applied for the implementation of health promotion in the hospital can grow and run regularly.Keyword: Health Promotion on Hospital, Ottawa Charter